Multi-stage terramechanics simulation: Seamless analyses between formation of wind ripple pattern and wheel locomotion. Issue 1 (1st January 2020) - Suzuki, Hirotaka; Ozaki, Shingo
Abstract: In futuristic vehicle traveling simulation on a rough terrain, it is desirable to perform terramechanics analysis that reflected appropriate road surface information. This paper presents a multi-stage analysis method that seamlessly performs the terrain formation process and trafficability evaluation. Simulation of wind-blown ripple formation based on cellular automaton was adopted as an example, and fields were created for terramechanics analysis. Then, trafficability characterization was performed with a single rigid wheel on virtually created terrain fields based on resistive force theory. The analysis results showed that the traveling performance of a single wheel could be evaluated for various terrain fields and under various traveling conditions. The multi-stage analysis method presented in this paper can be employed for simulations in extreme environments such as planetary surfaces, deserts, and disaster sites, where sensing is difficult.